Al Composition Dependence of Band Offsets for SiO2 on α-(AlxGa1−x)2O3. (25th November 2021) - Xia, Xinyi; Fares, Chaker; Ren, Fan; Hassa, Anna; von Wenckstern, Holger; Grundmann, Marius; Pearton, S. J.
Abstract : Valence band offsets for SiO2 deposited by Atomic Layer Deposition on α -(Alx Ga1-x )2 O3 alloys with x = 0.26–0.74 were measured by X-ray Photoelectron Spectroscopy. The samples were grown with a continuous composition spread to enable investigations of the band alignment as a function of the alloy composition. From measurement of the core levels in the alloys, the bandgaps were determined to range from 5.8 eV (x = 0.26) to 7 eV (x = 0.74). These are consistent with previous measurements by transmission spectroscopy. The valence band offsets of SiO2 with these alloys of different composition were, respectively, were −1.2 eV for x = 0.26, −0.2 eV for x = 0.42, 0.2 eV for x = 0.58 and 0.4 eV for x = 0.74. All of these band offsets are too low for most device applications. Given the bandgap of the SiO2 was 8.7 eV, this led to conduction band offsets of 4.1 eV (x = 0.26) to 1.3 eV (x = 0.74). The band alignments were of the desired nested configuration for x > 0.5, but at lower Al contents the conduction band offsets were negative, with a staggered band alignment. This shows the challenge of finding appropriate dielectrics for this ultra-wide bandgap semiconductor system.